Advances in building technology : proceedings of the International Conference on Advances in Building Technology, 4-6 December, 2002, Hong Kong, China - Anson, M.; Ko, J. M.; Lam, E. S. S. (Elsevier, 2002)
This set of proceedings is based on the International Conference on Advances in Building Technology in Hong Kong on 4-6 December 2002. The two volumes of proceedings contain 9 invited keynote papers, 72 papers delivered by 11 teams, and 133 contributed papers from over 20 countries around the world. The papers cover a wide spectrum of topics across the three technology sub-themes of structures and construction, environment, and information technology. The variety within these categories spans a width of topics, and these proceedings provide readers with a good general overview of recent advances in building research.